Budaya Siri’ Na Pacce dan Sipakatau dalam Interaksi Sosial Masyarakat Sulawesi Selatan - Auliah Safitri; Suharno Suharno (Universitas Andalas, 2020)
The plurality of Indonesian, besides becoming a property, also becoming a boomerang for the unity of a nation. The conflict that arises will not resolve if they are left casually. The disputes can be overcome and avoided if the society can build positive social interaction among fellow. Therefore, in facing conflicts, it is necessary to realize that an ethnic group is not a social group that must be considered by, however, a local knowledge that is store in a culture of ethnic groups. This research aims to determine the social interaction of South Sulawesi’s communities, namely the ethnic of Bugis, Makassar, Mandar, and Toraja. Those four ethnics have had cultural characteristics that have been being a customs and philosophies of their lives because they have normative elements values that can bind their members. This research is compiled through a literature study in which the data obtained from various books and journals. The result reveals that the ethnics of South Sulawesi have been building social interaction based on the culture of Siri’ Na Pacce and Sipakatau, which are the main foundation in building positive communication among fellow. Those cultures must be well implemented and maintained in building social interaction.